Investigating Design: A Review of Forty Years of Design Research. - Bayazit, Nigan (Design Issues)
Provides a summary of design research history concerning design methods and scientific approaches to design. Definition of design research according to L. Bruce Archer; Objectives of design research; Role of design methods in design research; Significance of the thesis in design methods by Christopher Alexander entitled "Notes on the Synthesis of Form" to architecture; Discussion of the development of scientific research in design.